Konflik Sertifikat Tanah Dan Bangunan (Barang Milik Daerah) Antara Hak Masyarakat Dengan Pemerintah Kota Malang - Faisal; Saiman; Ali Roziqin (Faculty of Social and Political Science, 2023)
Land is a important factor in human life. In human life, most of his life is very dependent on land. On land, humnas can live and build livable buildings. The existence of official residence land and buildings whose property rights are under the Malang City Government and the Ministry of Finance is a problem because the land and houses that will be built by a Government service office are still occupiet by several heirs of employees of the Malang City State Treasury Service Office who have retired. This study aims examine the dynamics of social conflict relate to Agrarian Affairs by the Community and the Government, the second is to find out how the community forms resistance to the government in defending land and building houses. This study uses a qualitative descriptive research method. The theory used is conflict theory. The results showed that the roots of land and house building conflicts were the lack of justice for the heirs of retired employees of the Malang City State treasury Service Office who had devoted themselves to the state for decades, as well as the absence of continue to occupy the land and building of the house, giving rise to a reaction from the Government to immediately vacate it.